Pengaruh Kepercayaan Dan Risiko Terhadap Minat Nasabah Menggunakan Mobile Banking Di PT. BNI Di Lubuk Alung - Indah Kasman (Universitas 45 Surabaya, 2023)
The purpose of this study was to determine the effect of trust and risk on customer interest in using mobile banking at PT. BNI in Lubuk Alung partially or simultaneously. This type of research is quantitative. The sample used amounted to 89 people. Data collection techniques are observation, questionnaires and looking at the literature. Based on the results of the study, it was found that partially the trust variable had a positive and significant effect on customers' interest in using mobile banking at PT. BNI in Lubuk Alung with a tcount (7.823) > ttable (1.662) and a significant value of 0.000 <0.05 and risk has a negative and significant effect on customers' interest in using mobile banking at PT. BNI in Lubuk Alung with a tcount (-2.172) < ttable (1.662) and a significant value of 0.033 <0.05. Trust and risk variables simultaneously have a positive and significant effect on customers' interest in using mobile banking at PT. BNI in Lubuk Alung with Fcount (7.493) > Ftable (3.10) and a significant value of 0.000 <0.05